Kompetensi Profesional Guru Mata Pelajaran Pendidikan Agama Islam di SMA Negeri 10 Kota Bengkulu - Penti Amelia Ismi; Suhirman Suhirman (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2023)
This study aims to describe professional competence and the factors that influence it in Islamic Religious Education subject teachers at SMA Negeri 10 Bengkulu City. This research method uses a qualitative type with a naturalistic approach, as well as data collection techniques using interviews, observation, and documentation. The results of the research in this thesis are: 1) The Professional Competence of PAI teachers at SMA Negeri 10 Bengkulu City has not been implemented optimally: a). Mastery of PAI teacher material is obtained from various sources (Al- Qur'an, hadith, scholars' opinions, and books) b) Mastery of SK and KD has not been implemented optimally due to changes in curriculum flow, difficulties in determining KKO, long time allocations, missed learning objectives, and several teachers unifying their learning tools. c) Material development is less creative because it only uses book media and lecture methods. d) Reflective actions in the form of PTK, teacher reflection, and reflection on students, and fellow teachers have not been carried out optimally. e) The use of ICT is well implemented in communicating using WhatsApp grub, while selfdevelopment has not been carried out optimally. 2) Factors that influence the professional competence of PAI teachers at SMA Negeri 10 Bengkulu City: (1) internal factors: a) The background of all PAI teachers comes from PAI graduates. b) The teaching experience of senior teachers has advantages in mastering the material, understanding children's characteristics, and motivating children, while junior teachers in using ICT. c) The state of health through programs of morning exercise, culture, healthy eating, and healthy UKS. d) The economic welfare of PNS and PPPK teachers is guaranteed, while honorary teachers receive relatively low salaries below the minimum wage. (2) External factors: a) Educational facilities already exist but are inadequate. b) Time discipline and task discipline have been implemented properly. c) Supervision of the principal through individual techniques and group techniques.